2020
DOI: 10.1088/1757-899x/884/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

IoT Based Temperature Control for Smart Mosque

Abstract: Malaysia is a country which has one of the biggest Muslim societies in the world, followed by a large number of mosques scattered in various places and these mosques have maintenance problems especially in energy consumption. Mosques normally experience sudden influx of users at five specified times throughout the day, and the use of the fans in the mosques is very inefficient and wasteful, corresponding with the five daily Islamic prayers. Regarding this matter, this project is conducted in order to reduce mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The temperature and the fan speed are displayed on the LCD screen. The result of the project showed that the speed of the fan is controlled as per the change in temperature remotely controlled via web browser and Apps [6].…”
Section: Applications Of Iot In Hvacmentioning
confidence: 99%
“…The temperature and the fan speed are displayed on the LCD screen. The result of the project showed that the speed of the fan is controlled as per the change in temperature remotely controlled via web browser and Apps [6].…”
Section: Applications Of Iot In Hvacmentioning
confidence: 99%